Expansão urbana, planejamento e mobilidade: os setores Jardins do Cerrado, as obras de intervenção no trânsito, transporte coletivo e a mobilidade do trabalhador, em Goiânia e região metropolitana (2010 - 2015) - Paiva, Gabriel Ramos (2016)
Metropolitan issues have gained prominence in recent years in Brazil. Among the main issues addressed about Metropolitan Regions, intrametropolitan mobility, government policies and public transport are continuous concerns in the analyzes developed in urban geography. This work develops an approach to the relationship between government policies and the demands of the population of Goiânia and its Metropolitan Region. Its analysis focuses on traffic intervention works, located on GO 070, 060 and 080 in Goiânia, urban expansion in the Jardins do Cerrado region and the daily mobility of the economically active population. It suffers daily from intra-metropolitan mobility problems, congestion and metropolitan public transport. The research analyzes the events from 2010 to 2015, such a temporal scale was defined as covering the period before and after urban interventions. The central issue of the work is whether the intervention works were really functional for the population that commutes daily in Goiânia and the Metropolitan Region, whether through collective or individual transport, this issue directly influences the organization and development of urban space.